TRABALHO, FAMÍLIA E MOBILIDADE SOCIAL: um estudo sobre sociabilidade operária - Lima, Jacob Carlos (Caderno CRH, 2006)
O artigo trata da experiência de um grupo de trabalhadores fabris na Paraíba, estado sem tradição industrial, marcado por altos índices de migração e miserabilidade de sua população, subemprego e desemprego. Através da análise de trajetórias profissionais e pessoais desses trabalhadores procura-se recuperar o significado atribuído ao trabalho na fábrica, a importância do grupo familiar e das redes sociais informais na busca e manutenção do emprego, sinônimo de mobilidade social possível, e acesso a direitos sociais. PALAVRAS-CHAVE: trabalho fabril; trajetórias profissionais; redes informais; família; mobilidade social; direitos sociais. Family, work and social mobility: A study on the worker’s sociability This paper deals with the experience of a group of workers in the textile industry in Paraíba, a brazilian state with no industrial tradition, whose population shows high rates of migration, impoverishment, under-employment and unemployment. The objective of this paper is to try recover the meaning of working in a textile industry, the importance of the family group and the social ties in the search and maintenance of a job, as a synonym of possible social mobility and access to social rights, by means of an analysis of the workers’ professional and personal paths. KEY WORDS: textile industry; professional paths; informal network; family; social mobility; social rights. Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br